2012
DOI: 10.1116/1.4710997
|View full text |Cite
|
Sign up to set email alerts
|

Novel surface chemical synthesis route for large area graphene-on-insulator films

Abstract: Articles you may be interested inLocal solid phase growth of few-layer graphene on silicon carbide from nickel silicide supersaturated with carbon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…[13] Members of our research team have recently reported an ovel methodf or synthesis of epitaxial graphene films that involves halogen-based plasma etchingo fS iC followed by ultrahigh vacuum annealing. [14] This produces single and multilayer graphene films with ah alogenated defect whose concentration can be controlled by the annealing temperature. Using nuclear magnetic resonance( NMR) and X-ray photoelectron spectroscopy (XPS), Ito and co-workers [15] have identified asimilar defecti nf luorine-graphite intercalation compounds (F-GICs).…”
Section: Introductionmentioning
confidence: 99%
“…[13] Members of our research team have recently reported an ovel methodf or synthesis of epitaxial graphene films that involves halogen-based plasma etchingo fS iC followed by ultrahigh vacuum annealing. [14] This produces single and multilayer graphene films with ah alogenated defect whose concentration can be controlled by the annealing temperature. Using nuclear magnetic resonance( NMR) and X-ray photoelectron spectroscopy (XPS), Ito and co-workers [15] have identified asimilar defecti nf luorine-graphite intercalation compounds (F-GICs).…”
Section: Introductionmentioning
confidence: 99%
“…High temperature processes are required to remove the residues. 4 Epitaxial growth on SiC 5 by the sublimation of Si atoms at high temperatures and high vacuum or by etching 6 on the other hand leads to better quality of graphene, but involves high costs in synthesis and subsequent transferring 7 of graphene to desired substrates. 8 Uniform epitaxial graphene layers can be deposited over large areas covered with catalytic metal layers, such as Ni, Pt, Ru, Ir, Cu, and Co, or metal carbides by chemical vapor deposition 9,10 of hydrocarbons as well as pulsed laser deposition 11 (PLD) using suitable targets, such as highly ordered pyrolytic graphite (HOPG).…”
mentioning
confidence: 99%
“…Following this approach, single, bi and trilayer films produced here were observed to have electrical resistivity values in the range of 1.6-6.4 µΩ-cm. The conductivity values for samples produced using Cl2-based plasma were in the same range [46]. Overall, these values are comparable to those reported by Murali and coworkers for exfoliated graphene nanoribbons [111].…”
Section: Electrical Characterizationsupporting
confidence: 87%
“…Raghavan et al studied graphene synthesis by using inductively coupled plasma-reactive ion etching (ICP-RIE) with the halogen based gases like Cl2 and CF4 [46]. Silicon was selectively removed from 6H-SiC substrate using halogen gases to produce a carbon rich layer on the substrate.…”
Section: Reactive Ion Etchingmentioning
confidence: 99%
See 1 more Smart Citation